Methane emission factors for enteric fermentation in beef cattle using IPCC Tier-2 method in Indonesia - Yeni Widiawati; M.N. Rofiq; B. Tiesnamurti (Indonesian Center for Animal Research and Development (ICARD), 2016)
Methane emission from enteric is a sub-category considered under the Agriculture sector greenhouse gas emissions by UNFCCC, thus Indonesia developed calculation on enteric CH4 EF for ruminant using Tier-2 method as country-specific emission factors (EF). Indonesia has huge amount of beef cattle population, which contributes significant amount to national enteric methane emission. The aim of this study was to estimate enteric methane EF for beef cattle in Indonesia using IPCC Tier-2 method. The EF generated from this study is then used to estimate the methane emitted from beef cattle. Data on beef cattle population was obtained from BPS, data on energy content of feed, feed intake and digestibility were compiled from laboratory analysis and published paper. Equations were adopted and followed the instruction of IPCC 2006. Local cattle has different CH4 EF among each sub-category, which are ranging from 18.18 to 55.89 Kg head-1 yr-1, with the average of 36.75 head-1 yr-1. Imported beef cattle has lower CH4 EF (25.49 kg head-1 yr-1) than the average for local beef cattle. Overall, the national CH4 EF of beef cattle calculated by using IPCC Tier-2 method in Indonesia is 33.14 head-1 yr-1. The value is lower than default EF from IPCC for Asia country (47 kg head-1 yr-1). The conclusion is enteric CH4 EF for beef cattle in Indonesia calculated using Tier-2 method shows the real livestock system in Indonesia condition. Further research needed to be addressed are calculation of EFs for various breeds and feeding systems, since large variations of breeds and types of feed among provinces in Indonesia.